Development of a digital educational platform in the process of training future professionals in the field of physical culture and sports - Petrov P.K. ,; Dmitriev O.B. ,; Akhmedzyanov E.R. , (Theory and Practice of Physical Culture, 2025)
Objective of the study – is to systematize the practical experience of creating a digital educational platform for training specialists in the field of physical culture and sports in the context of digitalization of education. The experience of the Udmurt State University is considered as an example. Methods and structure of the study. To write this article, approaches such as the study and systematization of scientific literature devoted to the digitalization of education in a broad sense and physical culture in particular were applied. In addition, a retrospective review of the development and formation of a digital educational platform in the process of training specialists in the field of physical culture and sports was conducted, based on the personal experience of the authors. Results and conclusions. Thearticleexamines the keyaspects of the formation of the digitaleducationalenvironment(DSP)in the context of the digitaltransformation of physicaleducation.Questions are raisedregarding the challenges that ariseduring the transitiontodigitaltechnologiesinphysicaleducationand the creation of a DSP,takingintoaccountchangesinthehighereducation system, the emergence of innovativesportsdisciplinesand the specifics of the field of "Physicalculture",focusedonpracticaltraining. The importance of developingdigitalcompetencies among bothstudentsandteachingstaffforeffectivetraining of specialists in demandin the digitaleconomy is emphasized. The analysis of the data obtained will make it possible to more effectively modernize the DSP in the system of training specialists in the field of physical culture and sports in various areas: organization of the educational process, scientific research, educational work, administrative management and improvement of the material and technical base of the university, taking into account the progress of modern digital technologies.